Wistar Kyoto Rats Display Anhedonia In Consumption but Retain Some Sensitivity to the Anticipation of Palatable Solutions - Wright, Rebecca L.; Gilmour, Gary; Dwyer, Dominic M. (Frontiers in Behavioral Neuroscience, 2020)
The Wistar Kyoto (WKY) rat has been proposed as a model of depression-like symptoms. However, anhedonia - a reduction in the response to normatively rewarding events – as a central depression symptom has yet to be fully assessed in this model. We compared WKY rats and Wistar controls, with stress-susceptibility examined by applying mild unpredictable stress to a subset of each group. Anhedonia-like behavior was assessed using microstructural analysis of licking behavior, where mean lick cluster size reflects hedonic responses. This was combined with tests of anticipatory contrast, where the consumption of a moderately palatable solution (4% sucrose) is suppressed in anticipation of a more palatable solution (16% sucrose). WKY rats displayed greatly attenuated hedonic reactions to sucrose overall, although their reactions retained some sensitivity to differences in sucrose concentration. They displayed normal reductions in consumption in anticipatory contrast, although the effect of contrast on hedonic reactions was greatly blunted. Mild stress produced overall reductions in sucrose consumption, but this was not exacerbated in WKY rats. Moreover, mild stress did not affect hedonic reactions or the effects of contrast. These results confirm that the WKY substrain express a direct behavioral analogue of anhedonia, which may have utility for increasing mechanistic understanding of depression symptoms.